An Experimental Study of Plastic Hinges and Joints in Thin-Walled Tubes - Matolcsy, M. (Engineering Transactions, 1981)
The paper discusses various modes of plastic failure of thin-walled prismatic tubes subjected to comparison and/or bending with particular application to the design or safe bus underframe and superstructure. For compressed tubes a critical length was determined experimentally separating regions of local and global loss of stability. For members subjected to bending, an empirical relation was proposed describing the relationship between the bending moment and the rotation angle at a hinge. The behaviour of tubular joints under combined compression and bending was also studied. The effect of imperfection was taken into account by introducing in the description of hinge characteristics the probability distribution functions.